Celowość rozwoju teorii zarządzania wiedzą w organizacji - Mesjasz, Czesław (Purposiveness of Development of Theory of Knowledge Management in Organization, 2006)
Analysis of the writings on the knowledge management allows to conclude that their authors frequently do not attempt to analyze such terms as knowledge or intellectual capital, etc. Intuitive categories become an instrument of communication or of a "scientific discourse". It may be stated that theory and practice of management are influenced by postmodernism, understood in a simplified form, as transfer of emphasis from the search for objective categories to the application of intersubjective categories in the communication, or in the discourse. Application of imprecisely defined notions frequently accompanies a situation, when it is visible that some authors do not understand the limitations stemming from reification of metaphors. The aim of the paper is to prove why it is necessary to understand better the theoretical foundations of knowledge management, and to show how better understanding of theory would help to improve methods of knowledge management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 154-164